History of “Fire,, Fire - Human- Origin of Dance Relationship and Nevruz (Fear in camps of distant past, The rhythm of tension and joy of life) - Şahin, Tahir Erdoğan (Fırat University, 2020)
Fire has been an important element in the culture of societies as well as being one of the necessary elements for living. In the face of predators in nature, the fire that forms a security circle has a gruesome, burning, fatal effect on humans, even if not as much as animals. It is difficult to think of people who recognize fire in their own nature to take it to indoor places without using it in natural and open spaces. The fire used inside the camp keeps the group members in a circle. The measure that determines the circle is the burning power, heating and the power of lighting at night. This geometry is the visual projection of the rotation around the volcano. Today, it is necessary to understand that in various folkloric figures including Nevrouz, the rotation around the fire goes back thousands of years

Ateş, yaşamak için gerekli unsurlardan biri olması yanı sıra toplumların kültüründe önemli yer tutmuş, farklı alan ve mekânlarda farklı ritüellere kaynak teşkil etmiştir. Doğadaki yırtıcılar karşısında güvenlik çemberi oluşturan ateşin hayvanlar kadar olmasa da insanlar üzerinde de ürkütücü, yakıcı, öldürücü bir etkisi vardır. Ateşi kendi doğası içinde tanıyan insanların onu doğal ve açık alanlarda kullanmadan, kapalı mekânlara taşımalarını düşünmek zordur. Kamp içinde kullanılan ateş, biçimsel olarak grup üyelerini daire hâlinde tutar. Daireyi belirleyen ölçü, ateşin yakma, ısıtma ve geceleri aydınlatma gücüdür. Bu geometri, yanardağın çevresinde yapılan dönüşün görüntüsel izdüşümüdür. Günümüzde “nevruz” dahil çeşitli folklorik figürlerinde ateş etrafında dönüşün, binlerce yıl öncesine gittiğini anlamak gerekir.
“ATEŞ”İN GEÇMİŞİ, ATEŞ - İNSAN- DANS İLİŞKİSİNİN KÖKENİ VE NEVRUZ (UZAK GEÇMİŞİN KAMPLARINDA KORKU, GERİLİM VE YAŞAMA SEVİNCİNİN RİTMİ)